2011
DOI: 10.14221/ajte.2011v36n2.4
|View full text |Cite
|
Sign up to set email alerts
|

‘New Directions for Traditional Lessons’: Can Handheld Game Consoles Enhance Mental Mathematics Skills?

Abstract: This paper reports on a pilot study that compared the use of commercial off-the-shelf (COTS) handheld game consoles (HGCs) with traditional teaching methods to develop the automaticity of mathematical calculations and self-concept towards mathematics for year 4 students in two metropolitan schools. One class conducted daily sessions using the HGCs and the Dr Kawashima's Brain Training software to enhance their mental maths skills while the comparison class engaged in mental maths lessons using more traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…A literature search on math and mobile learning studies between 2003 to 2015 yielded only seven quantitative studies-the results and the programme length of these studies varied. Three studies found a positive change in student self-concept and attitudes to maths (Main and O'Rourke 2011;Riconscente 2013;Wu et al 2006) and three studies found no significant improvement in students' attitudes (Jaciw et al 2012;Robertson 2010, 2011). Bray and Tangney (2016) found different results for various scales of maths attitudes: an improvement in students' affective engagement and attitudes towards technology, but no significant difference in students' behavioural engagement, mathematical confidence and confidence with technology.…”
Section: Literature On Mobile Learning and Mathematicsmentioning
confidence: 99%
“…A literature search on math and mobile learning studies between 2003 to 2015 yielded only seven quantitative studies-the results and the programme length of these studies varied. Three studies found a positive change in student self-concept and attitudes to maths (Main and O'Rourke 2011;Riconscente 2013;Wu et al 2006) and three studies found no significant improvement in students' attitudes (Jaciw et al 2012;Robertson 2010, 2011). Bray and Tangney (2016) found different results for various scales of maths attitudes: an improvement in students' affective engagement and attitudes towards technology, but no significant difference in students' behavioural engagement, mathematical confidence and confidence with technology.…”
Section: Literature On Mobile Learning and Mathematicsmentioning
confidence: 99%
“…This study replicates similar research conducted in Scotland by Miller and Robertson (2009; and a small scale pilot study completed by Main and O'Rourke (2011). The difference between this study and earlier research was that, through a series of semi-structured interviews and set observation periods, teacher behaviour was monitored and viewpoints on using this form of technology were ascertained.…”
Section: Methodsmentioning
confidence: 52%
“…While specifically targeted DGBL such as HGCs appear well suited for today's learners, before school administrators and classroom teachers are prepared to implement it, researchers must continue to provide empirical evidence that these approaches are effective with students and positively received by educators. A small scale study by Miller and Robertson (2009) and initial research by Main and O'Rourke (2011) highlighted significant differences in speed and accuracy of mental math recall and student self-concept between students that used a HGC and Dr Kawashima's Brain Training and those who used their normal routine for mental math skill development. While it would be folly to make generalisations from these small-scale studies, Miller and Robertson's (2011) recent research involving 634 primary aged students (ages 10-11) from 32 locations throughout Scotland provides clearer evidence of the benefits for students using this technology.…”
Section: The Teacher's Role When Using Computer Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the potential of DGBL for mentalmaths skill development we conducted a pilot study involving 59 primary students using HGCs (Handheld Game Consoles) utilising Dr Kawashima's Brain Training program (designed to develop mental alertness through a series of activities). The finding indicated that students using HGCs made significantly more improvement in mental-maths automaticity than those who developed skills via typical classroom approaches (Main & O'Rourke, 2011). In this article, we report on an extension of the earlier study.…”
Section: Introductionmentioning
confidence: 65%